Impact of silicon carbide device technologies on matrix converter design and performance - Safari, Saeed (2015)
The development of high power density power converters has become an important topic in power electronics because of increasing demand in transportation applications including marine, aviation and vehicle system. The possibility for greater power densities due to absence of a DC link is made matrix converter topologies more attractive for these applications. Additionally, with the emerging SiC device technology, the operating switching frequency and temperature of the converter can be potentially increased. The extended switching frequency and temperature range provide opportunities to further improve the power density of the power converters.